Determinants of glycaemic control in a practice setting: the role of weight loss and treatment adherence (The DELTA Study). Issue 11 (12th August 2014) - McAdam‐Marx, C.; Bellows, B. K.; Unni, S.; Mukherjee, J.; Wygant, G.; Iloeje, U.; Liberman, J. N.; Ye, X.; Bloom, F. J.; Brixner, D. I.
Summary: Aims: Examine the association between weight loss and adherence with glycaemic goal attainment in patients with inadequately controlled T2DM. Materials and methods: Patients ≥ 18 years with T2DM from a US integrated health system starting a new class of diabetes medication between 11/1/10 and 4/30/11 (index date) with baseline HbA1c ≥ 7.0% were included in this cohort study. Target HbA1c and weight change were defined at 6‐months as HbA1c < 7.0% and ≥ 3% loss in body weight. Patient‐reported medication adherence was assessed per the Medication Adherence Reporting Scale. Structural equation modelling was used to describe simultaneous associations between adherence, weight loss and HbA1c goal attainment. Results: Inclusion criteria were met by 477 patients; mean (SD) age 59.1 (11.6) years; 50.9% were female; 30.4% were treatment naïve; baseline HbA1c 8.6% (1.6); weight 102.0 kg (23.0). Most patients (67.9%) reported being adherent to the index diabetes medication. At 6 months mean weight change was −1.3 (5.1) kg (p = 0.39); 28.1% had weight loss of ≥ 3%. Mean HbA1c change was −1.2% (1.8) (p< 0.001); 42.8% attained HbA1c goal. Adherent patients (OR 1.70; p = 0.02) and diabetes therapies that lead to weight loss (metformin, GLP‐1) were associated with weight loss ≥ 3% (OR 2.96; p< 0.001). Weight loss (OR 3.60; p < 0.001) and adherence (OR 1.59; p < 0.001) were associated with HbA1c goal attainment. Conclusions: Weight loss ≥ 3% and medication adherence were associated with HbA1c goal attainment in T2DM; weight loss was a stronger predictor of goal attainment than medication adherence in this study population. It is important to consider weight‐effect properties, in addition to patient‐centric adherence counselling, when prescribing diabetes therapy.